Wheat Stripe Rust Resistance Protein WKS1 Reduces the Ability of the Thylakoid-Associated Ascorbate Peroxidase to Detoxify Reactive Oxygen Species. Issue 6 (19th May 2015) - Gou, Jin-Ying; Li, Kun; Wu, Kati; Wang, Xiaodong; Lin, Huiqiong; Cantu, Dario; Uauy, Cristobal; Dobon-Alonso, Albor; Midorikawa, Takamufi; Inoue, Kentaro; Sánchez, Juan; Fu, Daolin; et al.
Abstract : The wheat WKS1 protein reduces the activity of a chloroplast enzyme that detoxifies reactive oxygen species and causes cell death in the infected regions, conferring partial resistance to stripe rust. Abstract: Stripe rust is a devastating fungal disease of wheat caused by Puccinia striiformis f. sp tritici ( Pst ). The WHEAT KINASE START1 ( WKS1 ) resistance gene has an unusual combination of serine/threonine kinase and START lipid binding domains and confers partial resistance to Pst . Here, we show that wheat ( Triticum aestivum ) plants transformed with the complete WKS1 (variant WKS1.1 ) are resistant to Pst, whereas those transformed with an alternative splice variant with a truncated START domain ( WKS1.2 ) are susceptible. WKS1.1 and WKS1.2 preferentially bind to the same lipids (phosphatidic acid and phosphatidylinositol phosphates) but differ in their protein-protein interactions. WKS1.1 is targeted to the chloroplast where it phosphorylates the thylakoid-associated ascorbate peroxidase (tAPX) and reduces its ability to detoxify peroxides. Increased expression of WKS1.1 in transgenic wheat accelerates leaf senescence in the absence of Pst . Based on these results, we propose that the phosphorylation of tAPX by WKS1.1 reduces the ability of the cells to detoxify reactive oxygen species and contributes to cell death. This response takes several days longer than typical hypersensitive cell death responses, thus allowing the limited pathogen growth and restricted sporulation that is characteristic of the WKS1 partial resistance response to Pst.